Maturation of nematode-induced galls in Medicago truncatula is related to water status and primary metabolism modifications. (March 2015) - Baldacci-Cresp, Fabien; Maucourt, Mickaël; Deborde, Catherine; Pierre, Olivier; Moing, Annick; Brouquisse, Renaud; Favery, Bruno; Frendo, Pierre
Highlights: Identification of metabolites in mature galls induced by M. incognita. Ionic content analyze presents gall specificity. The gall aging affects the metabolomic and ionic content. Evolution of water status during gall aging and correlation to metabolism changes. Abstract: Root-knot nematodes are obligatory plant parasitic worms that establish and maintain an intimate relationship with their host plants. During a compatible interaction, these nematodes induce the redifferentiation of root cells into multinucleate and hypertrophied giant cells (GCs). These metabolically active feeding cells constitute the exclusive source of nutrients for the nematode. We analyzed the modifications of water status, ionic content and accumulation of metabolites in development and mature galls induced by Meloidogyne incognita and in uninfected roots of Medicago truncatula plants. Water potential and osmotic pressure are significantly modified in mature galls compared to developing galls and control roots. Ionic content is significantly modified in galls compared to roots. Principal component analyses of metabolite content showed that mature gall metabolism is significantly modified compared to developing gall metabolism. The most striking differences were the three-fold increase of trehalose content associated to the five-fold diminution in glucose concentration in mature galls. Gene expression analysis showed that trehalose accumulation was, at least, partially linked to a significantly lower expression of the trehalase gene in mature galls. Our results point to significant modifications of gall physiology during maturation.